Gambaran Mutu Blenderized Tube Feeding dengan Bahan Lokal Tinggi BCAA Berbasis Labu Kuning, Telur Ayam, dan Susu Kedelai (BUTESLA) - Rasyidah, Amira Farah; Mustikaningrum, Fitriana (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Liver cirrhosis is a chronic condition that often leads to malnutrition due to impaired intake, absorption, and metabolism. Malnutrition worsens disease progression and increases the risk of complications and mortality. Enteral nutrition is a key strategy to meet the nutritional needs of these patients; however, the high cost of commercial enteral formulas limits accessibility, especially in resource-constrained settings. This study aimed to develop and evaluate a locally sourced, high Branched-Chain Amino Acid (BCAA) enteral formula as a more affordable alternative for patients with liver cirrhosis. An experimental design was employed, and the study was conducted at the Nutrition Laboratory of Universitas Muhammadiyah Surakarta in May 2025. The formula was developed using pumpkin, chicken eggs, soy milk, and either tempeh (F1) or tuna (F2), and compared to a commercial enteral formula (FEK). Nutritional content was analyzed using Nutrisurvey 2007, osmolality with an Advanced Instruments osmometer, viscosity with a BrookField D-11+Pro viscometer, and flow rate using a 14 French nasogastric tube. Organoleptic tests were conducted using a hedonic scale and analyzed with Kruskal-Wallis and Mann-Whitney tests via SPSS 22.0. Formula F1 provided 1305.6 kcal of energy, 49 g of protein, 38.3 g of fat, 196.2 g of carbohydrates, and 9.3 g of BCAA, with an energy density of 1.3 kcal/cc. F1 showed an osmolality of 368 mOsm/kg, viscosity of 50.34 cP, and a flow rate of 1.00 cc/second, all meeting recommended standards. Sensory evaluation indicated that F1 was significantly preferred over F2 and FEK in terms of color, aroma, taste, texture, and overall acceptability (p < 0.05). The formula also offers a more affordable option without compromising nutritional quality. F1 is a promising alternative enteral formula based on local food ingredients for patients with liver cirrhosis, offering good nutritional value, excellent acceptability, and greater affordability.